Exploring Relational Politics in Social Learning: Dilemmas of standing too close to the fire - Paul Hart (Environmental Association of Southern Africa, 2007)
... a common theme amongst critics (of the dominant educational paradigm) is that problems with human- environment relationships (out there) are intimately linked to 'inner' problems, that is, our collective perception and thought processes are impeded by a lack of awareness of our 'in here' condition. (adapted from Sterling, 2003:118) Sterling's (2003) concern was that, because paradigms/worldviews/cultures/discourses function as ideologies that legitimise/justify courses of action, we need to learn how each of us is complicit politically in constructing subtexts by which our actions are judged to be reasonable. Such learning is not neutral and is contingent on processes of participation that engage people in thoughtful social action. One could say, as many environmental educators have for several decades, that at the core of environmental education is a relational view of learning. A purpose of this paper is to explore how such a view of learning is tied intimately to a person's identity/subjectivity, that is, to explore how what happens 'out there' and 'in here' are mutually constitutive.